2017
DOI: 10.1136/postgradmedj-2016-134599
|View full text |Cite
|
Sign up to set email alerts
|

Gender and international clinician educators

Abstract: Objectives To describe gender differences of international clinician educators (CEs) and leaders, and CEs’ perceptions by gender of preparation, roles, rewards and factors affecting job satisfaction and retention in emerging international competency-based residency programmes. Methods Cross-sectional surveys of CEs and leadership were conductedJune 2013–June 2014 at institutions that had adopted competency-based graduate medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…Studies suggest that physicians view teaching as intellectually stimulating, leading to increased job satisfaction . Further, structured residency training programs can provide physicians with educational leadership opportunities . However, given the long duration of medical training, many years to decades are needed for an expansion in undergraduate and postgraduate training capacity to have any considerable impact on the numbers of practicing physicians.…”
Section: Discussionsupporting
confidence: 91%
“…Studies suggest that physicians view teaching as intellectually stimulating, leading to increased job satisfaction . Further, structured residency training programs can provide physicians with educational leadership opportunities . However, given the long duration of medical training, many years to decades are needed for an expansion in undergraduate and postgraduate training capacity to have any considerable impact on the numbers of practicing physicians.…”
Section: Discussionsupporting
confidence: 91%
“…No studies beyond those identified were revealed by the 17 contacted scholars. Original data were available for 40 studies, described in 42 articles5 15 52–91 (see online supplementary material 1 for an overview of included studies).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies (n=35) were conducted in the USA, six included Canadian respondents,61 76 information on Canadian programmes,60 77 79 or schools’ leadership,55 one study was conducted across three countries (UAE, Qatar and Singapore),87 one study was conducted across three European countries (Sweden, the Netherlands and Austria),70 one study was conducted across four European countries (Germany, Sweden, Austria and the UK),71 one study in Norway72 and one study in Croatia 80. The earliest study was conducted in 1999,72 and more than 50% of the studies were published in the past 5 years alone.…”
Section: Resultsmentioning
confidence: 99%
“…7 Although most studies focus on Western contexts, international studies confirm gender disparities in the recruitment, retention, and advancement of women, with significant underrepresentation in academic leadership positions. 7,8 The promotion of women faculty to this educational leadership role is a step toward gender diversity, equity, and inclusivity in academic medicine in the Middle East. The majority of DIOs in this study held leadership and education roles prior to assuming the DIO position and felt well prepared for their GME leadership responsibilities.…”
Section: Discussionmentioning
confidence: 99%